Floor plan of John Ducey's store, Keels, NL. - Catherwood, Kristin; Millar, Edward; Whitney, Erin (2012)
John Ducey’s store was built by Humby’s Construction of Princeton in 1996, using locally cut wood. The building is oriented on a northeast-southwest axis, and is located a few feet northeast of his house. This store is primarily used for preparing, repairing, and storing John’s fishing equipment. All of the woodworking tools and materials needed to create and maintain his lobster and crab pots can be found in the store, along with cotton, nylon, and bio-degradable twine for the nets. The gear used for carrying out repairs on his speedboat and trap skiff while at sea are stored here in the off season.